Use of an Electrochemical Split Cell Technique to Evaluate the Influence of Shewanella oneidensis Activities on Corrosion of Carbon Steel - Iannuzzi, Mariano; Miller, R.; Sadek, A.; Rodriguez, A.; Giai, C.; Senko, J.; Monty, C. (Public Library of Science, 2016)
Microbially induced corrosion (MIC) is a complex problem that affects various industries. Several techniques have been developed to monitor corrosion and elucidate corrosion mechanisms, including microbiological processes that induce metal deterioration. We used zero resistance ammetry (ZRA) in a split chamber configuration to evaluate the effects of the facultatively anaerobic Fe(III) reducing bacterium Shewanella oneidensis MR-1 on the corrosion of UNS G10180 carbon steel. We show that activities of S. oneidensis inhibit corrosion of steel with which that organism has direct contact. However, when a carbon steel coupon in contact with S. oneidensis was electrically connected to a second coupon that was free of biofilm (in separate chambers of the split chamber assembly), ZRA-based measurements indicated that current moved from the S. oneidensis-containing chamber to the cell-free chamber. This electron transfer enhanced the O2 reduction reaction on the coupon deployed in the cell free chamber, and consequently, enhanced oxidation and corrosion of that electrode. Our results illustrate a novel mechanism for MIC in cases where metal surfaces are heterogeneously covered by biofilms.